Examination of machine tool slideway combined with pressure chambers - Tóth, Sándor Gergő; Takács, György (Design of Machines and Structures, 2020)
This paper deals with the preliminary functional testing of a novel combined slideway type. In order to improve the accuracy of a portal-type milling machine to be designed as part of a departmental project, special unloaded guideway designs have been investigated, resulting in a slideway structure relieved with hydraulic pressure chambers. A measuring bench was set up to check the amount of the relief. Based on the primary measurements performed, it is proven, that the pressure chambers relieves the load by providing a suitable sliding surface.